Environmental Impact Evaluation of a Fresh Milk Production - Agustin, Yulianti; Kurniawan, Miftakhurrizal; Astuti, Retno; Rahman, Mohammad Arifur (Industria: Jurnal Teknologi dan Manajemen Agroindustri, 2021)
AbstractThe study aimed to evaluate the waste impact on the environment in fresh milk production activities from the dairy cows rearing on farms to the distribution process of fresh milk to a milk processing factory and fresh milk selling agents, identify the most significant potential for contamination from fresh milk production activities on the environment, and provide alternative improvements based on the most significant environmental impact caused by fresh milk production activities. This research was conducted in a dairy farmer cooperative which is an organization that produces fresh milk. The Life Cycle Assessment (LCA) method was used to evaluate the environmental impact of fresh milk production activities. The analysis was carried out using SimaPro 9.0.0.47 software. The LCA stages carried out were Goal and Scope Definition, Life Cycle Inventory, Life Cycle Impact Assessment (LCIA), and Life Cycle Interpretation. The assessment of improvement alternatives was then analyzed using the pairwise comparison method to determine the highest weight. The results showed that the three most significant impact categories, namely eutrophication, human toxicity soil, and acidification. The biggest contamination from fresh milk production activities occurs in the fresh milk extraction process. Processing dairy cow dung into manure was the prioritized recommendation to reduce the impact.Keywords: environmental impact, life cycle assessment, fresh milk AbstrakPenelitian ini bertujuan untuk mengevaluasi dampak limbah terhadap lingkungan pada aktivitas produksi susu segar mulai dari pemeliharaan sapi perah di peternakan sampai pada proses distribusi susu segar ke pabrik pengolah susu dan agen penjual susu segar, mengetahui potensi cemaran terbesar dari aktivitas produksi susu segar terhadap lingkungan, dan memberikan alternatif perbaikan berdasarkan dampak lingkungan terbesar yang disebabkan oleh aktivitas produksi susu segar. Penelitian ini dilakukan di a dairy farmer cooperative yang merupakan suatu organisasi yang memproduksi susu dalam bentuk segar. Metode Life Cycle Assessment (LCA) digunakan untuk mengevaluasi dampak lingkungan dari kegiatan produksi susu segar. Analisis dilakukan dengan software SimaPro 9.0.0.47. Tahapan LCA yang dilakukan adalah Goal and Scope Definition, Life Cycle Inventory, Life Cycle Impact Assessment (LCIA), dan Life Cycle Interpretation. Penilaian alternatif perbaikan kemudian dianalisis menggunakan metode perbandingan berpasangan untuk menentuan bobot tertinggi. Hasil penelitian menunjukkan bahwa tiga kategori dampak tertinggi yaitu eutrhopication, human toxicity soil dan acidification. Cemaran terbesar dari kegiatan produksi susu segar terjadi pada proses ekstraksi susu segar. Pengolahan kotoran sapi perah menjadi pupuk kandang merupakan rekomendasi yang diprioritaskan untuk mengurangi dampak tersebut..Kata kunci: dampak lingkungan, life cycle assessment, susu segar